Status Asthmaticus in the Pediatric ICU: A Comprehensive Review of Management and Challenges - Amy Joseph; Hammad Ganatra (MDPI AG, 2024)
This narrative review addresses the significant burden of pediatric status asthmaticus, which comprises almost 20% of admissions to pediatric intensive care units (PICUs). It highlights the diverse modalities employed in the PICU for managing this life-threatening condition, and thoroughly discusses the literature in support of or against these treatment modalities.